The role of cytokines in the pathogenesis of SAPHO syndrome - Yang, Yi; Chen, Qianzhu; Zhong, Weiyang (Frontiers in Immunology, 2024)
SAPHO syndrome is a complex inflammatory disorder affecting the skin and bones, characterized by osteomyelitis, acne, and pustulosis. Cytokines play a pivotal role in the pathogenesis of SAPHO syndrome, especially in inflammatory responses and immune regulation. This article reviews the cytokines involved in the pathogenesis of SAPHO syndrome, such as tumor necrosis factor α (TNF-α), interleukin 1β (IL-1β), IL-6, IL-10, and transforming growth factor-β (TGF-β), and discusses their potential as intervention points for treatment. These findings elucidate the intricate immune regulatory network of SAPHO syndrome and provide a theoretical foundation for the development of new targeted therapeutic strategies.